Pemberian Salep Ekstrak Bunga Biduri (Calotropis gigantea) untuk Penyembuhan Luka pada Mencit (Mus musculus) Secara Klinis dan Histopatologis - Marphirah Marphirah (Biotik, 2018)
Milkweed (Calotropis gigantea) flower has some important compounds in wound healing such as alkaloids, flavonoids, tannins, karbohydrates, glikosides, phenols, saponins, protein and amino acid, and calothropin. The aim of this study was to determine the clinical and histopathological effect of milkweed extract ointment towards wound healing in mice (Mus musculus). The research was carried out in January to August 2018. This study used experimental method with Completely Randomized Design (CRD) with five treatments: betadine oinment as positive control, vaseline oinment as negative control, and three experimental treatment with milkweed extract ointments in 5%, 10% and 15% concentration. Every treatment contains of 6 mice each, which were wounded with 1 cm diameter excision on its back after injected with ketamine anesthesia. Data were analyzed using Analysis of Varians (ANOVA) and continued with Duncan Test α 0,05.  The clinical result showed that the fastest time of wound diameter reduction found on experimental treatment with 15% milkweed extract ointment. The histopathological result showed that the highest fibroblast number found on the experimental treatment with 15% milkweed extract ointment. It was concluded that the milkweed extract ointment have an effect on wound healing in mice clinically and histopathologically with 15% concentration being the best in promoting wound healing.